(untitled) (Research, Society and Development, 2021)
The thermal performance of a building is an important factor in homes when it is concerned with offering the user the thermal comfort that the user is entitled to have. A building must be designed for the climate in which it is inserted in order to have a greater potential in providing thermal comfort, and still save energy. This work aimed to evaluate the thermal performance, according to the guidelines of the Brazilian Performance Standard NBR 15575 of a single-family building located in the city of Águas Belas-PE, Brazil. The evaluation of thermal performance was performed through two procedures present in NBR 15575: the simplified procedure and the computational simulation. As a methodology, an exploratory research and a case study were carried out. The evaluation through the simplified method was given by calculations of thermal transmittance and thermal capacity of the building envelope, that is, of the facade walls and roof. The computational simulation was performed using the EnergyPlus program, which with climatic information and a three-dimensional model of the building was able to test the climatic conditions on the building and determine its thermal behavior. The results obtained through the analysis by the two procedures previously mentioned were compared and analyzed according to the requirements of NBR 15575, were small divergences between them was noted. Computer simulation proved to be more effective when compared to the simplified procedure.